The Effects of Skin Contact of Mother on Vital Signs and Behavioral State of Premature Neonates - Salimi; Shahbazi; Eslami; Dehghanpour (Iran University of Medical Sciences, 2009)
Background and Aim: Communication between mother and neonate is very important during neonatal period. One method of non verbal communication is skin contact of mother and neonate. The aim of this study was to examine the effects of skin contact of mother on vital signs and behavioral state of premature neonates hospitalized at Bahman and Shahid Sadoughi hospitals, Yazd.   Material and Method: In this clinical trial, samples were 50 premature neonates between 32-36 weeks of gestational age (25 in experimental group and 25 in control group). Data was collected via a demographic questionnaire, an observational check-list, and also, pulse rate, respiratory rate, and axillary temperature were recorded. The data was collected 10 minutes before and after skin contact between mother and premature neonate, in control group.   Results: There was no statistically significant difference between two groups in terms of weight, gestational age, sex, type of delivery and mother age. The results demonstrated that skin contact decreased pulse rate (P≤0.001) and respiratory rate (P≤0.001), increased axillary temperature (P=0.02) and had a positive effect on the behavioral state (P≤0.001).   Conclusion : The results suggest that skin contact between mother and premature neonate reduces pulse and respiratory rate and increases axillary temperature and have a positive effect on behavioral state of the neonate (ranges from arouse to deep sleep).